ISOLATION, CHARACTERIZATION AND ANTIBACTERIAL ACTIVITY OF ENDOPHYTIC BACTERIA FROM ADHATHODA BEDDOMEI - SWARNALATHA.Y; BHASWATI SAHA (International Journal of Pharma and Bio Sciences, 2014)
Adhathoda beddomei is used traditionally to treat various diseases. The endophytic bacteria present in the adhathoda may enhance its medicinal property.The current study concentrates to screen the endophytic bacteria from leaves of adhathoda beddomei. The surface sterilized leaves of the plant were used for the isolation of the endophytic bacteria. The isolates were identified using polymerase chain reaction using 16s ribosomal DNA (rDNA) method. Based on the similarity correlated with bacterial species and submitted to gen bank.From the obtained entophytic bacterial isolates only the pure culture was chosen for further analysis. The isolated bacteria were identified as enterobacter. The screened and isolated bacteria were concluded as enterbacter.